John Stuart Mill and the religion of humanity - Raeder, Linda C. (University of Missouri Press, 2002)
"John Stuart Mill and the Religion of Humanity introduces material that requires significant reevaluation of John Stuart Mill's contribution to the development of the liberal tradition." "John Stuart Mill and the Religion of Humanity examines the religious thought and aspirations of the philosopher and shows that, contrary to the conventional view of Mill as the prototypical secular liberal, religious preoccupations dominated his thought and structured his endeavors throughout his life. For a proper appreciation of Mill's thought and legacy, the depth of his animus toward traditional transcendent religion must be recognized, along with the seriousness of his intent to found a nontheological religion to serve as its replacement."--Jacket